Keeping IGF-II under control: lessons from the IGF-II-IGF2R crystal structure. - Brown, J; Jones, E; Forbes, B (2009)
Insulin-like growth factor-II (IGF-II) is a key regulator of cell growth, survival, migration and differentiation. Its pivotal role in these processes requires tight regulation of both expression and activity. The type 1 IGF receptor tyrosine kinase (IGF-1R) mediates IGF-II actions, and a family of six high affinity IGF binding proteins (IGFBPs) regulates IGF-II circulating half-life and its availability to bind IGF-1R. In addition, the type 2 IGF receptor (IGF2R; also called the cation-independent mannose-6-phosphate receptor) modulates the circulating and tissue levels of IGF-II by targeting it to lysosomes for degradation. The recently elucidated crystal structure of IGF-II-IGF2R complex provides new insight into IGF-II regulation, and reveals a common binding surface on IGF-II for the regulatory proteins, IGF2R and the IGFBPs.